Low caloric value of ethanol itself increases alveolar bone loss in ligature-induced periodontitis in male rats - de Souza, Daniela Martins (2009)
This study aimed at morphometrically evaluating the influence of variable caloric values of ethanol consumption on alveolar bone loss in periodontitis in male rats. Thirty-six male rats were randomized into four groups of nine rats each, as follows: Test group A (low) - rats were fed an ethanol-containing liquid diet (ethanol representing 22% of total caloric value); Control group A - rats were fed a pair-fed control diet (ethanol replaced by isocaloric amounts of carbohydrate); Test group B (high) - rats were fed an ethanol-containing liquid diet (ethanol representing 36% of total caloric value); Control group B - rats were fed a pair-fed control diet for Test B. Following anesthesia, cotton ligatures were placed around the cervix of the right upper second molar. At eight weeks, the maxillary bones were removed and alveolar bone loss was analyzed by measuring the distance between the cementoenamel junction and the alveolar bone crest at buccal and palatal sites of the upper second molar. The unligated groups showed no significant differences between the bone loss values observed for the low and high caloric values of ethanol (p > 0.05). In the ligated groups, the rats receiving low caloric values of ethanol showed significantly greater bone loss compared to the isocaloric rats (p < 0.05); however, the rats receiving high caloric values of ethanol showed no significant differences compared to the controls. Analysis of the results demonstrated that, in male rats, ethanol itself affected ligature-induced bone loss when representing a low value in the total caloric value.